Attitude of Service Provider in Tourism Industry Supply Chain toward the Positive Behavior to Encourage Guideline of Chinese Tourists in Thailand - ระบอบ ชุติระ; หมอยาดี ชณิชา; ทาระคำ พรวิสา; ไกรสำโรง อภิญญา (Business Administration and Management Journal Review, 2019)
This research aimed to study the attitude of service provider in tourism industry toward Chinese tourists to Thailand, analyze the character and behavior of them in the opinion of tourism industry in supply chain service provider and to propose the appropriate positive behavior to encourage guideline of Chinese Tourist in Thailand. The research tools were questionnaire and interview to hotel, restaurant and guide in Samut Prakran, Chonburi and Rayong provinces. 384 samples were selected by using purposive technique. Both quantitative and qualitative data were analyzed by using descriptive statistics, hypotheses testing and contents analysis. The research results revealed that service provider’s attitude toward Chinese tourists according to lack of understanding in Thai custom, behavior to annoy people. For the appropriate toward the positive behavior encourage are to give Thai culture understanding via guide tour leader and distribute Thai culture via website and tourists guide. The hypothesis testing found that there was no different in attitude and behavior of Chinese tourists. The appropriate guideline to encourage positive behavior of Chinese tourists found that it should be to give Thai cultural understanding, web site public relation and tourists guide book. Finding results showed that Chinese tourist from different sex, education level and place of birth make different positive behavior.